Can the rate of mortality and neurological recovery be predicted from the time of onset of symptoms and MRI grade in patients with cerebral fat embolism?: a study of 34 patients. (1st January 2022) - Armstrong, B. Roy W.; Devendra, Agraharam; Pokale, Shweta; Subramani, Bala; Rajesh Babu, Velmurugan; Ramesh, Perumal; Dheenadhayalan, Jayaramaraju; Rajasekaran, Shanmuganathan
Abstract : Aims: The aim of this study was to assess whether it is possible to predict the mortality, and the extent and time of neurological recovery from the time of the onset of symptoms and MRI grade, in patients with the cerebral fat embolism syndrome (CFES). This has not previously been investigated. Methods: The study included 34 patients who were diagnosed with CFES following trauma between 2012 and 2018. The clinical diagnosis was confirmed and the severity graded by MRI. We investigated the rate of mortality, the time and extent of neurological recovery, the time between the injury and the onset of symptoms, the clinical severity of the condition, and the MRI grade. All patients were male with a mean age of 29.7 years (18 to 70). The mean follow-up was 4.15 years (2 to 8), with neurological recovery being assessed by the Glasgow Outcome Scale and the Mini-Mental State Examination. Results: In all, seven who had early-onset CFES (< 24 hours), and a severe Takahashi grade on MRI, died. There was a significant association between the time of onset of neurological signs and mortality (p = 0.035). Mortality was also significantly associated with a severe Takahashi grade (p < 0.001). Among the 27 surviving patients, 26 (96.3%) recovered completely. One (3.7%) had a cognitive deficit. The mean time to recovery was 4.7 weeks (2 to 13), with late recovery aftereight eight weeks being recorded in three patients. Conclusion: There was a significantly increased rate of mortality in patients with CFES who had an early onset of symptoms and a severe grade on MRI. Complete neurological recovery can be expected in most patients with CFES who survive. Cite this article: Bone Joint J 2022;104-B(1):142–149.